2020
DOI: 10.3390/sym12060922
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Multi-Step Probability Selection Particle Swarm Optimization with Dynamic Chaotic Inertial Weight and Acceleration Coefficients for Numerical Function Optimization

Abstract: As a meta-heuristic algoriTthm, particle swarm optimization (PSO) has the advantages of having a simple principle, few required parameters, easy realization and strong adaptability. However, it is easy to fall into a local optimum in the early stage of iteration. Aiming at this shortcoming, this paper presents a hybrid multi-step probability selection particle swarm optimization with sine chaotic inertial weight and symmetric tangent chaotic acceleration coefficients (MPSPSO-ST), which can strengthen the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…24 benchmark test functions and two groups of engineering optimization experiments are adopted for testing the algorithm to evaluate its performance. e results suggest that the performance of CWDEPSO is better compared with PSO [22], DE [21], AIWCPSO [52], MPSPSO-ST [53], JADE [45], SinDE [54], and DEPSO [55] and five common metaheuristic algorithms GSA [12], ABC [11], MFO [7], SCA [6], and BBO [5]. Besides, it achieves the best performance in practical engineering optimization problems.…”
Section: Mobile Information Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 benchmark test functions and two groups of engineering optimization experiments are adopted for testing the algorithm to evaluate its performance. e results suggest that the performance of CWDEPSO is better compared with PSO [22], DE [21], AIWCPSO [52], MPSPSO-ST [53], JADE [45], SinDE [54], and DEPSO [55] and five common metaheuristic algorithms GSA [12], ABC [11], MFO [7], SCA [6], and BBO [5]. Besides, it achieves the best performance in practical engineering optimization problems.…”
Section: Mobile Information Systemsmentioning
confidence: 99%
“…Correspondingly, a larger inertial weight is helpful for global exploration, and with small inertia weight, it is conducive to local exploration. Afterwards, after many numerous studies [53,58,59], it was found that the nonlinear ω is more helpful for algorithm enhancement. In addition, in this paper, we choose to use nonlinear ω and perform chaos treatment, aiming to enhance the disorder during iteration to enhance the population diversity of the algorithm in the late iteration.…”
Section: Improvement Of Pso Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial positions and velocities of the particles in a classical setting are initialized randomly in the search space. Whereas, there exists a number of studies in literature suggesting different strategies for inertia and acceleration coefficients [46]- [48].…”
Section: A Classical Particle Swarm Optimization (Pso)mentioning
confidence: 99%
“…The swarm intelligence algorithm solves complex optimization problems by simulating the collective behavior of decentralized and self-organizing biological individuals in nature [24]. In recent years, a representative swarm intelligence algorithm called particle swarm optimization has been demonstrated to be an efficient optimization tool in solving non-convex complicated problems [25][26][27][28]. A comparison study of the PSO algorithm with a genetic algorithm in finding optimal portfolio solutions has been presented in [29] where several strategies for handling the constraints are designed.…”
Section: Introductionmentioning
confidence: 99%